Optimization of Tissue Decellularization Method Based on Macroscopic and Microscopic Observation in The Sheep Peripheral Nerves - Fajar Shodiq Permata; Rina Susilowati; Rini Dharmastiti; Muhammad Mirandy Pratama Sirat Mirandy Pratama Sirat; Pipin Dwi Kartikasari (Jurnal Sain Veteriner, 2012)
Animal graft tissue  (xenograft) was developed  to replace the limited supply of human graft tissue (allograft). Peripheral nerve graft tissue  is needed to replace  the damage. Swine is the most developed source of tissue donor for the preparation of acellular tissue because a lot of livestocks population and its extracellular matrix components similar to human collagen. Swine xenograft development would be an obstacle in Indonesia because of socio-cultural so that sheep used as swine donor replacement. Sheep cartilage tissue acellular induced less human inflammatory mediators than swine. Xenograft is necessary to decellularizebefore implantation into human that results in only extracellular matrix. However, decellularization process varies depending on the species and methods so that it is needed a preliminary study to get the best decellularization method for sheep peripheral nerve specimens. Five samples of sheep Ischiadicus  nerves were conducted decellularization various processes and one sample of fresh nerve (control). Decellularization methods were 24 hours shaking, tissue soaking and perfusion for both 14 days and 17 days, respectively. Decellularization solution was 0.1% SDS-EDTAin PBS. Post decellularization, samples were observed macroscopically, fixed, HE staining of histopathologic examination for microscopic examination. The data were analyzed descriptively. At the macroscopic observation of post decellularization tissue showed white, and samples of soaking method showed softer consistency than that of shaking and perfusion. Microscopic examination showed that samples were not being completed decellularization at shaking method. There was destruction of collagen fibers of perineurium and endoneurium in 17 days of soaking and perfusion methods, while 14 days soaking and perfusion methods showed that samples were being completed decellularization and both perineurium and endoneurium collagen were still good. Conclusion of this study is that 14 days soaking and perfusion decellularization methods are better than that of 24 hours shaking method and 17 days of soaking and perfusion methods for sheep decellularization peripheral nerve.